Task scheduling algorithm for system-wide information management based on multiple QoS constraints - Gang LI; Zhijun WU (Tongxin xuebao)
An ant colony optimization task scheduling algorithm based on multiple quality of service constraint (QoS-ACO) for SWIM was proposed.Focusing on the multiple quality of service (QoS) requirements for task requests completed in system-wide information management (SWIM),considering the task execution time,security and reliability factors,a new evaluate user satisfaction utility function and system task scheduling model were constructed.Using the QoS total utility evaluation function of SWIM service scheduling to update the pheromone of the ant colony algorithm.The simulation results show that under the same conditions,the QoS-ACO algorithm is better than the traditional Min-Min algorithm and particle swarm optimization (PSO) algorithm in terms of task completion time,security,reliability and quality of service total utility evaluation value,and it can ensure that the user's task scheduling quality of service requirements are met,and can better complete the scheduling tasks of the SWIM.